A Novel Simulation to Assess Residents' Utilization of a Medical Interpreter - Michael J. Zdradzinski (Association of American Medical Colleges, 2019)
Introduction Physicians must be facile in working with a medical interpreter (MI) given the large population of patients with limited English proficiency. Methods To facilitate residents' assessment of their ability to interact with non-English-speaking patients, we developed a simulation case involving one such patient. The case involved a 31-year-old Spanish-speaking postpartum female who presented with eclamptic seizures. The learner needed to request an MI to assist with obtaining the patient's medical history once her concerned family member (also Spanish speaking) arrived. The major critical actions included appropriate use of MI services, recognition of the risk for eclamptic seizures, proper evaluation and treatment, and appropriate disposition to an obstetrician. The case required a high-fidelity mannequin and simulation operator, nurse simulated participant, Spanish-speaking actor (to play the husband or family member), certified Spanish MI, and faculty evaluator. Results We implemented this case with 60 emergency medicine residents, ranging from PGY 1 to 3. The learner was assessed by both the faculty observer and MI. Checklists for assessment and debriefing materials were provided. Two of 60 residents did not request an MI. When compared to a prior version of this case that did not include the language barrier, median scores dropped from 12 to 10 out of 24, suggesting that the language barrier created a more challenging case. Discussion The use of MIs is an integral part of health care practice in the United States, and we present a simulation case that can assess learners' use of MIs.